A faster decline of residual kidney function and erythropoietin stimulating agent hyporesponsiveness in incident hemodialysis patients. Issue 1 (8th October 2020) - Kimura, Hiroshi; Sy, John; Okuda, Yusuke; Wenziger, Cachet; Hanna, Ramy; Obi, Yoshitsugu; Rhee, Connie M.; Kovesdy, Csaba P.; Kalantar‐Zadeh, Kamyar; Streja, Elani
Abstract: Introduction: Erythropoietin stimulating agents (ESA) hyporesposiveness has been associated with increased mortality in hemodialysis (HD) patients. However, the impact of decline of residual kidney function (RKF) on ESA hyporesposiveness has not been adequately elucidated among patients receiving HD. Methods: The associations of RKF decline with erythropoietin resistance index (ERI; average weekly ESA dose [units])/post‐dialysis body weight [kg]/hemoglobin [g/dL]) were retrospectively examined across four strata of annual change in RKF (residual renal urea clearance [KRU] < −3.0, −3.0 to <−1.5, −1.5 to <0, ≥0 mL/min/1.73 m 2 per year; urinary volume < −600, −600 to<−300, −300 to <0, ≥0 mL/day per year) using logistic regression models adjusted for clinical characteristics and laboratory variables in 5239 incident HD patients in a large US dialysis organization between 1 January 2007 and 31 December 2011. Findings: The median values of the annual change in KRU and urinary volume were −1.2 (interquartile range [IQR]: −2.8 to 0.1) mL/min/1.73 m 2 per year and −250 (IQR: −600 to 100) mL/day per year. A faster KRU decline in the first year of HD was associated with higher odds for ESA hyporesponsiveness: KRU decline of <−3.0, −3.0 to <−1.5, and −1.5 to <0/min/1.73 m 2 per year were associated with adjusted odds ratios (OR) of 2.07 (95% confidence interval [CI]: 1.66–2.58), 1.54 (95%CI: 1.28–1.85), and 1.26 (95%CI: 1.07–1.49), respectively (reference: ≥0 mL/min/1.73 m 2 per year). These associations were consistent across strata of baseline KRU, age, sex, race, diabetes, congestive heart failure, hemoglobin, and serum albumin. Sensitivity analyses using urinary volume as another index of RKF showed consistent associations. Discussion: A faster RKF decline during the first year of dialysis was associated with ESA hyporesponsiveness and low hemoglobin levels among incident HD patients.